Drug Abuse as a Ground for Divorce from the Perspective of Maqashid Syariah - Handika Utama Putra; Busman Edyar; Ilda Hayati; Rifanto Bin Ridwan (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to conduct an in-depth analysis of drug abuse as a triggering factor of divorce in Rejang Lebong Regency and to evaluate it through the perspective of Maqasid Sharia. The research employs a case study design with a sequential explanatory approach, integrating quantitative data obtained from the Religious Court of Curup with in-depth interviews involving divorced parties, customary leaders, and legal practitioners. The findings reveal two major conclusions. First, on an empirical level, drug abuse in Rejang Lebong has been identified as a systemic problem strongly associated with 15–30% of divorce petitions filed at the Religious Court of Curup over the past two years. Second, from the perspective of Maqasid Sharia, drug abuse systematically undermines the five universal objectives of Islamic law. It damages the intellect (hifzh al-‘aql) as the center of human consciousness, endangers life (hifzh al-nafs) through health risks and mortality, threatens lineage (hifzh al-nasl) by fostering an unhealthy family environment, and destroys property (hifzh al-mal) through financial waste on narcotics consumption. Accordingly, Islam views divorce in such circumstances not merely as a legal remedy, but as a necessary measure to safeguard greater public interest (maslahah), particularly the protection of life and the future of children, especially when the fundamental objectives of marriage tranquility and affection have been severely undermined. In this sense, divorce becomes a last-resort but legitimate mechanism to preserve the higher purposes of Sharia.